ILLOCUTIONARY ACT IN NICK VUJICIC SPEECH "OVERCOMING HOPELESSNESS” - Fa’ana, Yotam Sato Sanehura (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This research designed in descriptive qualitative research by using pragmatics approach. The aims of the research were to find out the types and meaning of each utterance which contains illocutionary act in Nick Vujicic speech “Overcoming hopelessness”. The researcher used Miles and Hubberman theory in analysing the data. The researcher focused to analyse the illocutionary aspect of the utterance, which divided in five types, declarations, representatives, expressives, directives, and commissives. Based on the analysis, the researcher found that there are only four types of illocutionary act in Nict Vujicic speech “Overcoming hopelessness” and the meaning of each utterance is always based on the context where the utterance spoken. Therefore, this research expect to be useful for teacher and student as the source information to give knowledge about illocutionary act in practical used especially teaching and learning activity.